The Role of Human Aldo-Keto Reductases in the Metabolic Activation and Detoxication of Polycyclic Aromatic Hydrocarbons: Interconversion of PAH Catechols and PAH o-Quinones - Zhang, Li; Jin, Yi; Huang, Meng; Penning, Trevor M. (Frontiers in Pharmacology, 2012)
Polycyclic aromatic hydrocarbons (PAH) are ubiquitous environmental pollutants. They are procarcinogens requiring metabolic activation to elicit their deleterious effects. Aldo-keto reductases (AKR) catalyze the oxidation of proximate carcinogenic PAH trans-dihydrodiols to yield electrophilic and redox-active PAH o-quiniones. AKRs are also found to be capable of reducing PAH o-quinones to form PAH catechols. The interconversion of o-quinones and catechols results in the redox cycling of PAH o-quinones to give rise to the generation of reactive oxygen species and subsequent oxidative DNA damage. On the other hand, PAH catechols can be intercepted through phase II metabolism by which PAH o-quinones could be detoxified and eliminated. The aim of the present review is to summarize the role of human AKRs in the metabolic activation/detoxication of PAH and the relevance of phase II conjugation reactions to human lung carcinogenesis.